Pengembangan Media Pembelajaran PowerPoint Interaktif untuk Keterampilan Menyimak Cerita Fiksi Kelas IV Sekolah Dasar - Sukmana, Mohamad Iqbal; Djuanda, Dadan; Syahid, Aah Ahmad (Jurnal Pena Ilmiah, 2021)
This research is based on the findings of the difficulties experienced by students in learning fiction listening skills caused by several factors. One of the factors is that teachers tend to only use the speech method and do not use more interactive learning media. The research method used is descriptive qualitative with a DD model research. Data were collected by interview, document analysis, expert validation of the media, and documentation. The results showed that the media commonly used at SDN Gudang Kopi II was still dominant in conventional visual media so that it was non-flexible. The design of this interactive learning media development with the waterfall development model, is conceptualized with the tutorial type and includes audio-visual interactive multimedia. As for the expert review/validation of the development of interactive powerpoint learning media, the final round by design experts significantly to 95.66%. The final round of material experts significantly to 93,85%. The final round of teacher as a user significantly to 95.55%. This means that interactive powerpoint learning media is very feasible to use based on the conversion of assessment criteria.